Chlamydia trachomatis seroprevalence atlas of Finland 1983–2003. Issue 1 (2nd October 2007) - Lyytikäinen, E; Kaasila, M; Koskela, P; Lehtinen, M; Patama, T; Pukkala, E; Tasanen, K; Surcel, H-M; Paavonen, J
Abstract : Objectives: To study Chlamydia trachomatis seroprevalence trends and geographical distribution over time in Finland. Materials and methods: First pregnancy serum samples were retrieved from the Finnish Maternity Cohort serum bank for the subcohort of 8000 women stratified by calendar years (1983–1989, 1990–1996, 1997–2003) and age at time of sample withdrawal (14–22 and 23–28 years). C trachomatis antibodies were determined using standard major outer membrane protein peptide ELISA. The spatiotemporal variation of C trachomatis seroprevalence rates was visualised by a series of maps. Results: A decreasing C trachomatis seroprevalence trend from 1983 to 2003 was seen for both women under 23 years of age (20.8% to 10.6%) and 23–28-year-old women (19.1% to 12.5%). Constant clusters were seen around the largest cities and in eastern Finland although seroprevalence rates were generally decreasing throughout the country. Conclusions: Only a few population-based serological studies have been undertaken on C trachomatis epidemiology over time. In Finland the seroprevalence of C trachomatis is decreasing all over the country, albeit with small clusters remaining.